Brain‐derived neurotrophic factor genotype is associated with brain gray and white matter tissue volumes recovery in abstinent alcohol‐dependent individuals. (11th October 2012) - Mon, A.; Durazzo, T. C.; Gazdzinski, S.; Hutchison, K. E.; Pennington, D.; Meyerhoff, D. J.
Abstract : Neuroimaging studies have linked the methionine (Met) allele of the brain‐derived neurotrophic factor ( BDNF ) gene to abnormal regional brain volumes in several psychiatric and neurodegenerative diseases. However, no neuroimaging studies assessed the effects of this allele on brain morphology in alcohol use disorders and its demonstrated change during abstinence from alcohol. Here we assessed the effects of the BDNF Val66Met (rs6265) polymorphism on regional brain tissue volumes and their recovery during short‐term abstinence in treatment‐seeking alcohol‐dependent individuals. 3D T1 weighted magnetic resonance images from 62 individuals were acquired at 1.5 T at one week of abstinence from alcohol; 41 of the participants were rescanned at 5 weeks of abstinence. The images were segmented into gray matter (GM), white matter (WM) and cerebrospinal fluid and parcellated into regional volumes. The BDNF genotype was determined from blood samples using the TaqMan technique. Alcohol‐dependent Val (Valine)/Met heterozygotes and Val homozygotes had similar regional brain volumes at either time point. However, Val homozygotes had significant GM volume increases, while Val/Met heterozygotes increased predominantly in WM volumes over the scan interval. Longitudinal increases in GM but not WM volumes were related to improvements in neurocognitive measures during abstinence. The findings suggest that functionally significant brain tissue volume recovery during abstinence from alcohol is influenced by BDNF genotype. Abstract : BDNF Val66Met polymorphism modulates brain lobar gray and white matter volume recovery in short‐term alcohol‐dependent individuals (Frontal gray and white matter longitudinal volume changes in Val homozygotes and Val/Met heterozygotes between TP1 and TP2)